2009
DOI: 10.1029/2008ja013722
|View full text |Cite
|
Sign up to set email alerts
|

Charge states of energetic ions in Jupiter's radiation belt inferred from absorption microsignatures of Io

Abstract: [1] The Heavy Ion Counter on the Galileo Jupiter orbiter observed depletions of energetic (^5 MeV/nucleon) oxygen and sulfur ions near Io that are interpreted as absorption microsignatures. The two elements were equally abundant in this region of Jupiter's radiation belt. Numerical simulations of microsignatures from Galileo orbits 27, 31, and 32, based on calculations of ion trajectories in models of the magnetospheric and Alfvén wing magnetic fields, show that the data are most consistent with the ions being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 24 publications
(30 reference statements)
2
19
1
Order By: Relevance
“…We propose that ion-neutral interactions are playing a role in redistributing the energetic (>hundreds of keV) heavy ion charge states near the trans-Europa cloud and inward. This idea reconciles the observational differences that show the charge states of energetic oxygen are primarily O + at large distances (this work and Allen et al, 2019), a more even mixture of O + and O ++ is found near the neutral cloud (Clark, Mauk, et al, 2016), and a maximum charge state value of O 8+ is found near Io (Selesnick & Cohen, 2009). 5.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We propose that ion-neutral interactions are playing a role in redistributing the energetic (>hundreds of keV) heavy ion charge states near the trans-Europa cloud and inward. This idea reconciles the observational differences that show the charge states of energetic oxygen are primarily O + at large distances (this work and Allen et al, 2019), a more even mixture of O + and O ++ is found near the neutral cloud (Clark, Mauk, et al, 2016), and a maximum charge state value of O 8+ is found near Io (Selesnick & Cohen, 2009). 5.…”
Section: Discussionsupporting
confidence: 90%
“…We propose that ion‐neutral interactions are playing a role in redistributing the energetic (>hundreds of keV) heavy ion charge states near the trans‐Europa cloud and inward. This idea reconciles the observational differences that show the charge states of energetic oxygen are primarily O + at large distances (this work and Allen et al, 2019), a more even mixture of O + and O ++ is found near the neutral cloud (Clark, Mauk, et al, 2016), and a maximum charge state value of O 8+ is found near Io (Selesnick & Cohen, 2009). The recent overview from Mauk et al (2020) showing that megavolt potentials span most of the polar cap area (see our Figure 1, magenta curves) and the analysis of the associated heavy ions in this paper, we believe this supports the hypothesis of soft X‐ray emissions that are sourced by precipitating energetic heavy ions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nénon and André (2019) demonstrated that energetic ion charge states likely evolve with energy and distance from Jupiter. Selesnick and Cohen (2009) suggest that at the highest energies, heavy ions may be fully ionized.…”
Section: Particle Tracing Model Gentoomentioning
confidence: 99%
“…The jovian plasma and energetic charged particle environment is composed of an admixture of hydrogen, sulfur, and oxygen ions (e.g., Krupp et al, 2004; Mauk et al, 2004; Thomas et al, 2004). Associated heavy ion charge states are predominately O + and S ++ ; however, studies have shown that this may vary with energy and/or distance from Jupiter (e.g., Allen et al, 2019; Clark et al, 2016; Selesnick & Cohen, 2009).…”
Section: Introductionmentioning
confidence: 99%